Development and validation of a social robot anthropomorphism scale (SRA) in a french sample. Issue 162 (June 2022) - David, Dayle; Hayotte, Meggy; Thérouanne, Pierre; d'Arripe-Longueville, Fabienne; Milhabet, Isabelle
Highlights: This study introduces the social robot anthropomorphism scale in French, adapted to the specificities of social robots. This scale proposes an integrative approach to anthropomorphism. The psychometric qualities of the SRA scale were demonstrated. Results showed a link between anthropomorphism of social robots and acceptability and negative attitudes towards robots.